Enhanced Carbon Sequestration in Marginal Land Upon Shift towards Perennial C4Miscanthus × giganteus: A Case Study in North-Western Czechia - Karim Suhail Al Souki; Hana Burdová; Jakub Trubač; Jiří Štojdl; Pavel Kuráň; Sylvie Kříženecká; Iva Machová; Karel Kubát; Jan Popelka; Hana Auer Malinská; Diana Nebeská; Sergej Ust’ak; et al. (Agronomy, 2021)
Bioenergy crops such as Miscanthus × giganteus are foreseeable as an alternative source to replace fossil fuel and reduce greenhouse gas emissions. They are also assessed as an environment-friendly solution for polluted, marginal and low-quality agricultural soils. Several studies had been launched on soil organic carbon sequestration potentials of miscanthus culture along with its impacts on restoring soil functionality, most of which focus on the long-term basis of the plant’s cultivation. Nevertheless, information concerning the short term impacts as well as the situation in Czechia is still scarce. In this context, a field experiment was launched in 2017 in a poor-quality agricultural land in the city of Chomutov (North-Western Czechia) to compare the impacts of the perennial C4 miscanthus with an annual C3 forage crop (wheat) on the soil carbon stocks as well as enhancing its functionality. Results through the 0–30 cm soil profile examination showed that miscanthus plants played a role in improving the studied soil physico-chemical (bulk density and soil organic carbon concentrations) and biological (Phospholipid fatty acids stress indicator, basal respiration and fluorescein diacetate hydrolytic activity) parameters. The naturally occurring δ13C concentrations were used to evaluate the direct plant contribution to the total soil organic carbon (SOC) stocks and revealed considerable miscanthus contribution all over the detected soil layers (1.98 ± 0.21 Mg C. ha−1 yr−1) after only 3 growing seasons. It is thus suggested that the C4 perennial miscanthus possess remarkable prospects for SOC sequestration and restoring degraded lands.